The Development of Plants Booklet in Cilongok District, Banyumas Regency as a Learning Supplement for Classification of Living Things for Junior High Schools (Journal of Biology Education, 2023)
During the Covid-19 pandemic, learning at SMP Negeri 2 Cilongok was carried out online. Material for classification of living things is science learning material for class VII in the 2013 curriculum. The teaching materials used in the form of textbooks and Student Worksheets (LKS) are not able to help students understand the material and study independently because they have not utilized plants in the surrounding environment. The types of plants in Cilongok District, Banyumas Regency have the potential as a source of learning, but the use of plants as a source of learning directly requires a longer time. Therefore a learning supplement is developed that is easy to understand and easy for students to use for independent study, namely the Plants Booklet in Cilongok District, Banyumas Regency which contains pictures and descriptions. The research aims to identify plant species in Cilongok District, Banyumas Regency, to analyze the validity and readability of booklets as learning supplements. The method used is Research and Development (R&D) research. The booklet product trial was carried out at Cilongok 2 Public Middle School involving class VII F students and science teachers. Based on the results of the identification of plant species in Cilongok District, Banyumas Regency, 60 species were found that were relevant to be used as learning resources in Plantae material. The results of material and media validation in the booklet showed very good results with a percentage of material validation of 81.3% and media validation of 96.5%. The booklet readability test showed a high category with an average percentage of 83.3%. Based on the results of the study it can be concluded that the Plant Booklet in Cilongok District, Banyumas Regency was stated to be valid and easily understood by students to be used as a supplement to learning material on the classification of living things.